Mythologies of martial arts - Bowman, Paul 1971- (Martial arts studies, 2017)
From kung fu to jujitsu and from Bruce Lee to the Karate Kid, Mythologies of Martial Arts explores key myths and ideologies of martial arts in contemporary popular culture. This book combines the author's practical, professional and academic experience in martial arts to offer new insights into this complex, often contradictory world. Inspired by the work of Roland Barthes in Mythologies, this book focuses on the signs, signifiers and practices of martial arts globally. Bringing together cultural, film, media and post colonial studies with the emerging field of martial arts studies, this book explores the broader significance of martial arts in global culture. Using an accessible yet theoretically sophisticated style, Mythologies of Martial Arts is ideal for students, scholars and anyone interested in any type of martial arts.